PENGARUH KEPEMIMPINAN KEPALA MADRASAH DENGAN BUDAYA BELAJAR DAN PRESTASI BELAJAR PESERTA DIDIK - Nurjannah Majid; Abd . Pirol; Fauziah Zainuddin (Institut Agama Islam Negeri (IAIN) Palopo, 2021)
This reseach focuses on the problem, there are: 1) is there affect of the madrasah head leadership on learning culture and learning achievement of students in Madrasah Aliyah Negeri (MAN) Palopo, 2) is there a relationship between the learning culture and student achievement in learning with the head of Madrasah Aliyah Negeri (MAN) Palopo State Leaders. This research uses quantitative research and the analysis formula of Simple Linear Regression or often referred to as SLR (Simple Linear Regression). The data of this research are in the form of madrasah principals leadership in developing student learning culture and student achievement. The population of this research was 838 student. There are 27 classes. The researcher took 100 students as sample of research. The variable of the research are madrasah principals leadership as the independent variable (x). While those as the dependent variables are learning culture (Y1) and learning achievement (Y2). Base on the result of the t test calcutaion. Analysis shows that there is a significant influence of variables (x) on learning culture (Y1) and learning achievement (Y2). It evidences by the result of the calculation of t count of 1,075 and 283 compare to t table (df =100) which is 0,667 significant level of 5%. So when thitung > ttabel them H1 is accepted and H0 is rejected. It means that there is an influence of madrasah leadership between culture of learning and learning achievement of students with the head of Madrasah Aliyah Negeri (MAN) palopo. The implivation of this researh to accept a positive learning culture and learning avhievement to relate with the students’ personal personaly talents, and the absorption of a negative culture will have implicatins that can be derrimental to individual and others in the palopo Aliyah Negeri Madrasah (MAN) environment.